Claim for damages and effective administration of justice regarding embezzlement convictions in Moquegua, 2016. - Barrera Apaza, Katerin (2021)
The purpose of this research is to determine how much the non-compliance of a judgment ordering damages affects the right to effective administration of justice in the embezzlement convictions in the Judicial District of Moquegua, 2016. Non-experimental research, cross-sectional study, and logical inductive-deductive methods were used. This study examined the writs of execution aimed at putting into force judgements handed down in connection with the crime of embezzlement by the Superior Court of Justice of Moquegua in 2016; and, by the lawyers from the Anti-Corruption Public Prosecutor’s Office of Moquegua. The results allowed to conclude that the high level of non-compliance of judgements ordering damages affects the right  to effective administration of justice in the embezzlement convictions in the Judicial District of Moquegua, 2016.